2005
DOI: 10.1021/ma0487352
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cocontinuous Morphologies in Initially Heterogeneous Thermosets Blended with Poly(methyl methacrylate)

Abstract: Morphology and phase separation process in blends of a network-forming reactive polymer, poly(aminopropylmethylsiloxane) (PAMS), in a poly(methyl methacrylate) (PMMA)-modified epoxy system were studied using optical, epifluorescence and scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), and dynamic mechanical thermal analysis (DMTA). The thermoset system was bisphenol A diglycidyl ether (DGEBA) with different PMMA percentages, 2-10% w/w. Phase separation and reaction advancement were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…mid-IR (mIR) as well as near-IR (nIR) show characteristic peaks corresponding to oxirane groups and amines in the region 600 cm -1 to 4000 cm -1 and 4000 cm -1 to 7000 cm -1 respectively. Taking advantage of this special feature, many researchers 14,19,20 have used these techniques for monitoring curing reactions. Concentrations of above mentioned four species in the curing reaction are linearly related to peak area ratios in the IR region 21 and therefore their intensities can be used (to calculate area) to follow the mechanism of curing 5,20,[22][23][24][25][26] .…”
Section: Curing Reaction and Ftir Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…mid-IR (mIR) as well as near-IR (nIR) show characteristic peaks corresponding to oxirane groups and amines in the region 600 cm -1 to 4000 cm -1 and 4000 cm -1 to 7000 cm -1 respectively. Taking advantage of this special feature, many researchers 14,19,20 have used these techniques for monitoring curing reactions. Concentrations of above mentioned four species in the curing reaction are linearly related to peak area ratios in the IR region 21 and therefore their intensities can be used (to calculate area) to follow the mechanism of curing 5,20,[22][23][24][25][26] .…”
Section: Curing Reaction and Ftir Correlationmentioning
confidence: 99%
“…In this study to observe phase separation in the system, they showed that the baseline change in FTIR is associated with change in the blend transparency to the near-IR radiation 39 . using same principle Cabanelas 14 , et al studied progress of a continuous network of PMMA in DGEBA. Figure 8 (a) shows FTIR spectra of DGEBA/PMMA/PAMS (poly(am inopropylmethylsiloxane)) system with corresponding increase in baseline as a function of epoxy conversion in Fig.…”
Section: Ftir To Observe Phase Separationmentioning
confidence: 99%
“…A different approach using perfunctionalized polysiloxanes such as poly(3-aminopropylmethylsiloxane) has been recently reported [4][5][6]. A complex reactive compatibilization process seems to give rise to quasi-homogeneous fullycured materials but the question about their morphology and its evolution during cure remains open.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, this method has also been used to follow compatibilization of initially immiscible systems. As an example Cabanelas et al (Cabanelas et al, 2005) studied the compatibilization process and phase separation of a third component in reactive blends based on DGEBA and poly(3-aminopropylmethylsiloxane) modified with PMMA. As shown in Figure 12, the initial decrease of the baseline was related with the compatibilization between DGEBA and the silicone hardener and the subsequent increase was related with the onset of phase separation of the thermoplastic modifier.…”
Section: Phase Separation Influence On Ir Spectramentioning
confidence: 99%